Postmenopausal women with higher TSH values within the normal range present improved handgrip strength: a pilot study - Panagiota Chatzivasileiou; Eleni Armeni; Peter Chedraui; Loraina Kontou; Areti Augoulea; Anastasia Palaiologou; George Kaparos; Konstantinos Panoulis; Andreas Alexandrou; Nikolaos Vlachos; Irene Lambrinoudaki (Gynecological Endocrinology)
Objective To evaluate the possible association between thyroid function within the euthyroid range and musculoskeletal parameters as well as body composition in a sample of postmenopausal women.Methods This cross-sectional study included 96 postmenopausal women with serum thyroid-stimulating hormone (TSH) within the normal laboratory reference range. Fasting venous blood samples were obtained for biochemical/hormonal assessment. Bone status and body composition were measured using Dual Energy X-ray absorptiometry (DXA). Physical activity was quantified using the International Physical Activity Questionnaire (IPAQ) index.Results Serum TSH correlated with handgrip strength (HGS, r-coefficient = 0.233, p = .025), and total body bone mineral density (BMD) T-score values (r-coefficient = 0.321, p = .003). HGS measures were associated with BMD (r-coefficient = 0.415, p < .001), with bone mineral content (BMC, r-coefficient = 0.427, p < .001), and lean mass (r-coefficient = 0.326, p = .003). Women with low muscle strength, defined as HGS < 16 kg, had lower TSH levels than women with normal muscle strength (low vs. normal muscle strength, ANCOVA 1.13 ± 0.49 mU/L vs. 1.60 ± 0.83 mU/L, p = 0.024) independently of age, BMD, percentage of body fat or absolute lean mass. Multivariable linear regression analysis showed that HGS values were associated with TSH measurements (β-coefficient = 0.246, p = .014) and BMD T-score values (β-coefficient = 0.306, p = .002). All models were adjusted for age, body mass index (BMI), vitamin D, low-density lipoprotein cholesterol, current smoking, physical activity, and homeostasis model assessment of insulin resistance.Conclusions In this sample of postmenopausal women, lower serum TSH values, within normal range, were associated with lower muscle strength compared to higher normal TSH values. Further research is needed to elucidate the significance of our preliminary findings.